Reproductive biology of the tropical fish Trichogaster pectoralis (Regan) - Hails, A.J.; Abdullah, Z. (Wiley Blackwell, 1982)
The breeding cycle of an air‐breathing Anabantid, Trichogaster pectoralis was studied in Malaysia. The species was found to breed all the year but with pronounced peaks of activity associated with the two wetter periods in the year. The advantages of this timing and the cues which stimulate gonadal activity are discussed. From the study of oocyte distribution in selected ovaries it was concluded that T. pectoralis is a total spawner although a batch of ripe oocytes may be released over an extended period of time. Fecundity was found to be related to length of fish by the formula (log10 Egg no.)=–4.6854+4.3080 log10 standard length (S.L.) (mm).